2022
DOI: 10.3389/fonc.2022.906125
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Screening for Second Primary Tumors of the Esophagus Among Head and Neck Cancer Patients

Abstract: Malignancies of the head and neck (HN) region and esophagus are among the most common cancers worldwide. Due to exposure to common carcinogens and the theory of field cancerization, HN cancer patients have a high risk of developing second primary tumors (SPTs). In our review of 28 studies with 51,454 HN cancer patients, the prevalence of SPTs was 12%. The HN area is the most common site of SPTs, followed by the lungs and esophagus, and 13% of HN cancer patients have been reported to have esophageal high-grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…22 Among the various SPMs, EC is one of the most common, with prevalence rates of 0% to 31.5%, (average 0.9%). 21 The prevalence of EC varies among studies due to differences in study design, the primary sites of HNSCC, and the prevalence of HPV-related HNSCC. 22,23 Several studies found the risk of second primary EC to be higher in the hypopharyngeal region compared to other subsites, 21,24 and the incidence of SPMs was lower in HPV-related HNSCC compared to non-HPV-related HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Among the various SPMs, EC is one of the most common, with prevalence rates of 0% to 31.5%, (average 0.9%). 21 The prevalence of EC varies among studies due to differences in study design, the primary sites of HNSCC, and the prevalence of HPV-related HNSCC. 22,23 Several studies found the risk of second primary EC to be higher in the hypopharyngeal region compared to other subsites, 21,24 and the incidence of SPMs was lower in HPV-related HNSCC compared to non-HPV-related HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The upper aerodigestive epithelium is the most common site of SPMs due to field cancerization, indicating exposure to similar carcinogens in cigarette smoke, alcohol, and betel nuts 22 . Among the various SPMs, EC is one of the most common, with prevalence rates of 0% to 31.5%, (average 0.9%) 21 . The prevalence of EC varies among studies due to differences in study design, the primary sites of HNSCC, and the prevalence of HPV‐related HNSCC 22,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine screening in the work-up and follow-up of patients with OSCC could detect more early-stage SPTs. The diagnosis of SPTs may impact the management and treatment of tumors [ 34 ].…”
Section: Diagnostic Modalities For Second Primary Tumorsmentioning
confidence: 99%
“…According to a previous report, the incidence of second primary EC in patients with HNC is 9.7% [3]. Although there were no well-designed prospective studies to establish appropriate surveillance programs for second primary EC in HNC patients, several previous studies recommended routine screening esophagogastroduodenoscopy (EGD) for the early detection of metachronous EC in patients with a history of HNC [4][5][6].…”
Section: Introductionmentioning
confidence: 99%